2018
DOI: 10.1016/j.jad.2018.07.085
|View full text |Cite
|
Sign up to set email alerts
|

Child maltreatment, psychopathological symptoms, and onset of diabetes mellitus, hypothyroidism and COPD in adulthood

Abstract: The associations between retrospectively-reported CM and physical health outcomes in adulthood are partially driven by psychopathological symptoms in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…The potential confounding and mediating variables, age, sex, parental history of psychiatric problems/asthma/dementia, education, smoking, social support, and respondent's mental health, were chosen based on a priori knowledge of the correlates of childhood adversity and asthma and chronic bronchitis [1,5,7,8,11,[23][24][25][66][67][68]. With reference to the literature on mediation analysis, if there are any measured variables that may confound the mental healthasthma/chronic bronchitis association (e.g., education, smoking, and social support) and are affected by childhood adversity, then they should be included in the multivariable regression model as confounding variables.…”
Section: Confounding Variablesmentioning
confidence: 99%
See 3 more Smart Citations
“…The potential confounding and mediating variables, age, sex, parental history of psychiatric problems/asthma/dementia, education, smoking, social support, and respondent's mental health, were chosen based on a priori knowledge of the correlates of childhood adversity and asthma and chronic bronchitis [1,5,7,8,11,[23][24][25][66][67][68]. With reference to the literature on mediation analysis, if there are any measured variables that may confound the mental healthasthma/chronic bronchitis association (e.g., education, smoking, and social support) and are affected by childhood adversity, then they should be included in the multivariable regression model as confounding variables.…”
Section: Confounding Variablesmentioning
confidence: 99%
“…Several population-based studies have shown that childhood adversity is associated with an increased risk of stress-related physical health outcomes, such as asthma and chronic bronchitis later in life [1][2][3][4][5][6][7][8]. The role of mental health in the association of childhood adversity with onset of asthma and chronic bronchitis has been hypothesized in two ways: (1) mediation, whereby childhood adversity is associated with an increased risk of mental health problems, which in turn are associated with an increased risk of asthma and chronic bronchitis [8] (figure 1a); and (2) confounding and differential recall bias, i.e., psychological state of respondents at the time of reporting childhood adversity [7] may confound the association of retrospective childhood adversity with self-reported asthma and chronic bronchitis [1] (figure 1b). When considering the mediation hypothesis, childhood adversity can certainly affect mental health [8,9], while simultaneously affecting onset of asthma and chronic bronchitis via psychogenic relationships [1,3,7,8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not always possible to measure the underlying mental or emotional state on which the survey responses are based (Stommel & Wills, 2004). While there is ample evidence to suggest that “mental health” mediates the association between childhood adversity and COPD and migraine (Sheikh, 2018a) and that a person’s current “mood/psychological state” may confound this relationship (Sheikh et al, 2016b), mental health and mood/psychological state are two different, yet partly overlapping constructs. Since these constructs overlap, it is difficult to separate the mediation mechanism from the confounding mechanism (Sheikh, 2018d).…”
Section: Introductionmentioning
confidence: 99%